Why am I Doing My Thesis? An Explorative Study on Factors of Undergraduate Thesis Performance in Indonesia - Surya Cahyadi; Miryam Wedyaswari; Erna Susiati; Rasni Adha Yuanita (Universitas Ahmad Dahlan, 2021)
Writing an undergraduate thesis is a formidable task, especially in Indonesia where writing is not engrained in its culture. Therefore, this study aims to explore the internal and external factors in writing an undergraduate thesis. A qualitative research design was used. Phase 1 used an online questionnaire (n= 143) to find encouraging and obstructing factors. Phase 2 used an in-depth interview (n = 48) to validate findings from Phase 1. A general inductive approach was used to analyze data. Phase 1’s findings were students’ perceptions about undergraduate thesis and categories of encouraging and obstructing factors in writing a thesis. Writing undergraduate thesis was more driven by external factors (e.g.deadlines, others' expectations) than by internal factors. Neglect of writing the thesis, however, was caused more by internal factors (e.g. lack of knowledge and skills, doing other activities). Phase 2’s findings validated phase 1’s findings which consist of 11 encouraging and 8 obstructing factors.Keywords: Undergraduate thesis performance, undergraduate research, writing a thesis, university students, qualitative exploratory study